Public Native America : tribal self-representations in casinos, museums, and powwows - Lawlor, Mary, 1949- (Rutgers University Press, 2006)
The Native American casino and gaming industry has attracted unprecedented American public attention to life on reservations. Other tribal public venues, such as museums and powwows, have also gained in popularity among non-Native audiences and become sites of education and performance. In Public Native America, Mary Lawlor explores the process of tribal self-definition that the communities in her study make available to off-reservation audiences. Focusing on architectural and interior designs as well as performance styles, she reveals how a complex and often surprising cultural dynamic is cre.